Design of Liquid Formulation Based on F127-Loaded Natural Dimeric Flavonoids as a New Perspective Treatment for Leishmaniasis - da Costa, Camila Silva; Marques, Estela Mesquita; do Nascimento, Jessyane Rodrigues [UNESP]; Lima, Victor Antônio Silva; Santos-Oliveira, Ralph; Figueredo, Aline Santana; de Jesus, Caroline Martins; de Souza Nunes, Glécilla Colombelli; Brandão, Clenilma Marques; de Jesus, Edson Tobias; Sa, Mayara Coelho; Tanaka, Auro Atsushi; et al. (MDPI, 2024)
Infectious and Parasitic Diseases (IPD) remain a challenge for medicine due to several interconnected reasons, such as antimicrobial resistance (AMR). American tegumentary leishmaniasis (ATL) is an overlooked IPD causing persistent skin ulcers that are challenging to heal, resulting in disfiguring scars. Moreover, it has the potential to extend from the skin to the mucous membranes of the nose, mouth, and throat in both humans and various animals. Given the limited effectiveness and AMR of current drugs, the exploration of new substances has emerged as a promising alternative for ATL treatment. Arrabidaea brachypoda (DC). Bureau is a native Brazilian plant rich in dimeric flavonoids, including Brachydin (BRA), which displays antimicrobial activity, but still little has been explored regarding the development of therapeutic formulations. In this work, we present the design of a low-cost liquid formulation based on the use of Pluronic F127 for encapsulation of high BRA concentration (LF-B500). The characterization techniques revealed that BRA-loaded F127 micelles are well-stabilized in an unusual worm-like form. The in vitro cytotoxicity assay demonstrated that LF-B500 was non-toxic to macrophages but efficient in the inactivation of forms of Leishmania amazonensis promastigotes with IC50 of 16.06 µg/mL. The results demonstrated that LF-B500 opened a new perspective on the use of liquid formulation-based natural products for ATL treatment.
Keywords: Arrabidaea brachypoda; leishmaniasis; pluronic F127